Theoretical and Lexicographic Aspects of Studying Antonymy in Russian and Uzbek Languages - D. X., Eshmurodov (European Journal of Life Safety and Stability (2660-9630), 2021)
The article examines the theoretical and lexicographic aspects of the study of antonymy in the Russian and Uzbek languages, identifying not only the general patterns of development of this linguistic phenomenon, but also the specific features of its implementation in each studied language, as well as the formulation and solution of the following general theoretical problems: the connection between the linguistic and logical opposition , semantic classification of antonymic oppositions according to common, common for different languages, criteria, study of the mechanism of occurrence of antonyms in language and speech.